Sumur Gali Gambaran Risiko Pencemaran Dan Kandungan Coliform Air Sumur Gali Di Kenagarian Gurun Panjang Kapuh Kecamatan Koto XI Tarusan - Putri, Aenea Dwi; Suksmerri, Suksmerri; Riviwanto, Muchsin; Mahaza, Mahaza; Darwel, Darwel (Jurnal Kesehatan Lingkungan Mandiri, 2023)
Dug wells are the main source of clean water supplies for people living in rural and urban areas of Indonesia. The clean water used by the people of the Panjang Kapuh Desert generally comes from dug wells and drilled wells. In Village Gurun Panjang Kapuh, there are many dug wells that do not meet the construction requirements of dug wells, so they can pose a risk to clean water consumed by the community. The purpose of this study was to obtain an overview of the risk of pollution and coliform content of dug well water in the Village Gurun Panjang Kapuh, Koto XI Tarusan District, Pesisir Selatan Regency in 2022. This research is descriptive with a population of all houses that have clean water facilities dug wells as many as 730 dug wells. Data obtained from the results of the sanitary inspection of dug wells using the sanitation inspection form, in 85 dug wells 7 samples of dug well water were taken for water biology examination (Coliform) in the laboratory. Generally, there is a high risk of contamination of dug wells (69.4%). The total biological content (Coliform) of dug well water from 7 samples, 6 of which did not meet the requirements. It is recommended to the public to make or repair the well construction so that it has a good construction to prevent contamination of dug wells. Health workers should provide counseling and supervise dug well sanitation inspections and periodically check the biological quality of dug well water.